Decision regret in men living with and beyond nonmetastatic prostate cancer in the United Kingdom: A population‐based patient‐reported outcome study. Issue 5 (26th February 2020) - Wilding, Sarah; Downing, Amy; Selby, Peter; Cross, William; Wright, Penny; Watson, Eila K.; Wagland, Richard; Kind, Paul; Donnelly, David W.; Hounsome, Luke; Mottram, Rebecca; Allen, Majorie; et al.
Abstract: Objective: Clinical options for managing nonmetastatic prostate cancer (PCa) vary. Each option has side effects associated with it, leading to difficulty in decision‐making. This study aimed to assess the relationship between patient involvement in treatment decision‐making and subsequent decision regret (DR), and quantify the impact of health‐related quality of life (HRQL) outcomes on DR. Methods: Men living in the United Kingdom, 18 to 42 months after diagnosis of PCa, were identified from cancer registration data and sent a questionnaire. Measures included the Decision Regret Scale (DRS), Expanded Prostate cancer Index Composite short form (EPIC‐26), EQ‐5D‐5L, and an item on involvement in treatment decision‐making. Multivariable ordinal regression was utilized, with DR categorized as none, mild, or moderate/severe regret. Results: A total of 17 193 men with stage I‐III PCa completed the DRS: 36.6% reported no regret, 43.3% mild regret, and 20.0% moderate/severe regret. The odds of reporting DR were greater if men indicated their views were not taken into account odds ratio ([OR] = 6.42, 95% CI: 5.39‐7.64) or were involved "to some extent" in decision‐making (OR = 4.63, 95% CI: 4.27‐5.02), compared with men who were "definitely" involved. After adjustment, including for involvement, men reporting moderate/big problems with urinary, bowel, or sexual function were more likely to experience regret compared with men with no/small problems. Better HRQL scores were associated with lower levels of DR. Conclusions: This large‐scale study demonstrates the benefit of patient involvement in treatment decision‐making for nonmetastatic PCa. However, men experiencing side effects and poorer HRQL report greater DR. Promoting engagement in clinical decision‐making represents good practice and may reduce the risk of subsequent regret.